2016
DOI: 10.4236/oalib.1102294
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Performance of Some Rice (Oryza sativa L.) Varieties in Two Different Environments

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…In this regard, the correlation coefficient, which provides a symmetrical measurement for the degree of association between two variables or characters, which lead to comprehending the nature and magnitude of association among yield and yield components (Al-Daej, 2022). These results were match the findings of Al-Salim et al, (2016) who reported that, number of grains per plant, 1000-grains weight, number of productive tillers per plant and number of tillers per plant was positively correlated with grain yield, although not significantly. At the same time, the number of panicles per plant was highly positive correlation with spikelet fertility %.…”
Section: Phenotypic Correlation Coefficientssupporting
confidence: 91%
“…In this regard, the correlation coefficient, which provides a symmetrical measurement for the degree of association between two variables or characters, which lead to comprehending the nature and magnitude of association among yield and yield components (Al-Daej, 2022). These results were match the findings of Al-Salim et al, (2016) who reported that, number of grains per plant, 1000-grains weight, number of productive tillers per plant and number of tillers per plant was positively correlated with grain yield, although not significantly. At the same time, the number of panicles per plant was highly positive correlation with spikelet fertility %.…”
Section: Phenotypic Correlation Coefficientssupporting
confidence: 91%
“…In the present investigation, the grain yield showed positive and significant association with the number of tillers per plant, number of productive tillers per plant, number of filled grains per panicle, the total number of grains per panicle and spikelet fertility in both the crosses in F 2 , (Table 1 and 2). The positive and significant association of number of tillers per plant with single plant yield was reported by Gopikannan andGanesh (2013), Touhiduzzamam et al (2016) and Singh et al (2016); the number of productive tillers per plant with grain yield per plant by Krishnamurthy et al (2014); the number of filled grains per panicle with grain yield per plant by Singh et al (2016) and Pradhan et al (2017);the total number of grains per panicle with grain yield per plant by Gunasekaran et al (2010), Shiva Prasad et al (2013 and Singh et al (2016) Salim et al (2016); panicle length with grain yield per plant by Vanniarajan et al (1996) and Gopikannan and Ganesh (2013).…”
Section: Fig 2 Phenotypic Correlation Coefficients Between Yield and Yield Components In Crossmentioning
confidence: 99%
“…However, genotype-environment interaction usually hampers selection of such genotype due to the failure of genotype to show the same characteristic in different environment, since the environmental factors are usually in continuous state of change in both space and time. The understanding of genotype and environment interaction in plant breeding is a matter of major importance (Hammoud andGabr, 2014 andAl-Salim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%